Adherence to Life’s Essential 8 is associated with lower risk of hyperuricemia among adults in Beijing, China - Deng, Rui; Duan, Jiali; Yu, Bo; Zhang, Yan; Yao, Yihong; Ma, Rui; Sha, Yimei (Frontiers in Nutrition, 2026)
BackgroundHyperuricemia is linked to various cardiovascular diseases, yet evidence on the association of Life’s Essential 8, a newly updated metric for cardiovascular health, with hyperuricemia in the general Chinese population remains scarce.MethodsData were obtained from 1,519 adults in Beijing as part of the Chinese Nutrition and Health Surveillance 2022. Logistic regression and restricted cubic spline models were used to assess the associations of Life’s Essential 8 score and its subscales with the risk of hyperuricemia. Stratified analyses by key demographic variables were also performed.ResultsThe prevalence of hyperuricemia was 13.76%. For every 10-unit increase in Life’s Essential 8 score and its subscale of health factor scores, the risk of hyperuricemia decreased by 24% (OR = 0.76, 95% CI = 0.66 ~ 0.87) and 23% (OR = 0.77, 95% CI = 0.70 ~ 0.84), respectively. Participants with high Life’s Essential 8 scores had a lower risk of hyperuricemia compared with those with low Life’s Essential 8 scores (OR = 0.32, 95% CI = 0.14 ~ 0.74), and similar results were found for those with high health factor scores (OR = 0.29, 95% CI = 0.17 ~ 0.49). These associations were more pronounced among participants who had high educational levels and middle-class annual household incomes.ConclusionOur study revealed a negative association of the Life’s Essential 8 score with the risk of hyperuricemia in the general population of Beijing, China, which was also observed for its health factor subscale, highlighting the promise of adherence to the Life’s Essential 8 to maintain cardiovascular health and thereby reduce the disease burden of hyperuricemia.